ANALISIS PEKERJAAN RECEPTION DI HOTEL HORISON YOGYAKARTA - Yuningsih, Sri (RC-INSTITUT, 2019)
This research aimed to find out the assignments conducted by receptionist in Horison Hotel, Yogyakarta. This research is qualitative descriptive research. The data collection techniques were interviews, observation, and documentation. Based on the result, it was found that there were someassignmentsrelated to reception position in Horison Hotel Yogyakarta, they were:keeping the rooms which have been reservedby the guests who wanted to check-in immediately, conducting showing room, and coordinating information to the head for every problem or incident occurred beyond his/her authority. The result showed that it was only 60% of the reception employee in Horison Hotel who conducted their assignments.